Inscriptions: Narrating the Spatial Dynamics of the Immaterial Interior - Wahid, Arif Rahman; Paramita, Kristanti Dewi; Yatmo, Yandi Andri (UI Scholars Hub, 2021)
This paper explores inscription as a projection of the spatial dynamics of a setting, beyond a historical or cultural symbol in a context, and highlights that inscription—a written or carved message on a surface—is an element that immaterially demonstrates a more in-depth narrative of an interior. This paper focuses on exploring inscriptions embedded in various production settings in Jakarta and Central Java, collecting individual and observational accounts on the production of such inscriptions and their meanings. The study suggests that inscriptions demonstrate various roles, from providing information, mediating different spaces and performing as tools to assist activities. Inscriptions may traverse the trajectories of different spaces and exist in different layers of time, creating an interior connection across space and time. These layers and trajectories project the dynamics of material and bodily processes, assembling the immaterial interior.